2000
DOI: 10.1159/000055284
|View full text |Cite
|
Sign up to set email alerts
|

Scattered Fat Invasion: An Indicator for Poor Prognosis in Premenopausal, and for Positive Estrogen Receptor in Postmenopausal Breast Cancer Patients

Abstract: Background: Intracrine mechanisms which accelerate cancer cell growth are becoming well known in breast cancer research. In this study, microscopic invasive patterns of breast cancer cells into surrounding stromal tissues were evaluated. Patients and Methods: 174 patients (110 patients ≤50, and 64 ≧60 years) underwent total or partial mastectomy from 1985 to 1993. In these patients the microscopic invasive pattern (especially scattered invasion into fat, SIF), influence on hormone receptor status, survival, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Most of the data report a positive correlation with poor patient outcome. This is the case not only for breast cancers (Kimijima et al, 2000;Yamaguchi et al, 2008), but also for prostate, pancreas, kidney and colon cancers (Rio, 2011). Experimental data report a similar pejorative impact of adipocytes on cancer progression.…”
Section: In Vivo Evidence That Adipocytes Favor Tumor Progressionmentioning
confidence: 98%
“…Most of the data report a positive correlation with poor patient outcome. This is the case not only for breast cancers (Kimijima et al, 2000;Yamaguchi et al, 2008), but also for prostate, pancreas, kidney and colon cancers (Rio, 2011). Experimental data report a similar pejorative impact of adipocytes on cancer progression.…”
Section: In Vivo Evidence That Adipocytes Favor Tumor Progressionmentioning
confidence: 98%
“…Several in vitro studies have demonstrated that AT supports and promotes tumor growth. Moreover, the degree of tumor infiltration into the adjacent fat AT serves as histological criterion reflecting the aggressiveness of the tumor and is indicative of poor prognosis [58,59]. A special role in this matter can be attributed to mature AT fraction.…”
Section: Evidence Of the Pro-tumorigenic Effect Of The Adipocyte-tumomentioning
confidence: 99%
“…It was shown that scattered invasion into fat tissues (Kimijima, Ohtake, Sagara, Watanabe, & Takenoshita, 2000) and the invasive length of fat invasion (Hasebe, Imoto, Sasaki, & Mukai, 1998), (Hasebe, Mukai, Tsuda, & Ochiai, 2000) were related to a poor prognosis of ductal breast carcinoma. These observations were recently confirmed by Yamaguchi et al showing that adipose tissue invasion of cancer cells at the margin of the tumor mass is indeed one of the biologic indicators of tumor aggressiveness and poor prognosis (Yamaguchi, Ohtani, Nakamura, Shimokawa, & Kanematsu, 2008).…”
Section: Resolving the Adipocyte-cancer Cross-talkmentioning
confidence: 99%